Ergonomic Risk Prevention Model by applying PHA, HIRARC Matrix and OWAS Method in a Construction Sector: A Case Study - Acosta-Aguilar, Ariana Domysé; Polo-Villar, Marly Isabel; Corzo-Chavez, Jorge Antonio (LACCEI, 2025)
The construction sector has a high occupational incidence rate, mainly due to musculoskeletal injuries caused by ergonomic risk factors in the various construction site activities. This research aims to identify these risks in the construction process of concrete elements and develop an occupational health and safety model using the tools PHA, the HIRARC matrix, and the OWAS method, to reduce the rate of musculoskeletal injuries and occupational incidents. The proposed model includes the use of technical data sheets, checklists for machinery maintenance, and the proper use of personal protective equipment (PPE). In addition, ergonomic measures such as the use of lumbar belts and knee pads were implemented, along with safety, occupational health, and ergonomics training specific to the construction site environment. In addition, visual materials were developed, such as informative posters on the correct use of PPE and stretching exercises, promoting both risk prevention and workers’ well-being. The results obtained revealed significant improvements in the key indicators of the company under study. The rate of musculoskeletal injuries decreased from 26.67% to 13.33%, while the rate of occupational incidents decreased from 46.67% to 3.33%. These advances reflect a considerable positive impact on workers’ health and safety. The project is financially viable and profitable, with a Net Present Value (NPV) of USD 4,451.20, indicating that the financial returns outweigh the investment made.